Analisis Kejahatan Siber Sebagai Kejahatan Perang Berdasarkan Hukum Humaniter Internasional - Faris Meode Togatorop; Dwi Putri Lestarika; Wevy Sari (GLOBAL SCIENTS PUBLISHER, 2025)
This article discusses cybercrime as a form of war crime under international humanitarian law. Cyber crime is a phenomenon that is increasing along with the rapid development of information and communication technology. This crime includes various forms of illegal actions such as online fraud, data theft, data destruction, ransomware attacks, and illegal information dissemination that harm individuals, organizations, and countries. Handling cybercrime requires solid international cooperation and harmonization of legal norms at the national and global levels. International legal instruments such as the Budapest Convention and the 2001 Cybercrime Convention serve as an important basis in regulating and tackling these crimes. In addition, the role of international legal instruments such as the Budapest Convention and the 2001 Cybercrime Convention in regulating and tackling cybercrime at the global level is explained. The study emphasizes the need for international cooperation and harmonization of national laws in order to address the growing complexity of cybercrime. In general, this study highlights the challenges of law enforcement in the digital era and the importance of effective regulation in accordance with the principles of human rights and international humanitarian law. cybercrime that develops as a form of war crime requires a regulatory framework that is in accordance with the principles of international humanitarian law. Therefore, a sustainable effort is needed